Relationship between lactate levels and 28-day mortality in pediatric sepsis: results from the pediatric intensive care database - Yongfu Song; Na Wang; Xiaofei Xie; Yuxin Tian; Yongji Wang (BMC, 2024)
Abstract Objective This study aimed to investigate the relationship between serum lactate levels at admission to the intensive care unit (ICU) and the clinical outcomes of children with sepsis. Methods We used the Pediatric Intensive Care (PIC) database to identify 288 pediatric patients with sepsis. We analyzed the relationship between lactate levels and hospital and ICU mortality in sepsis by establishing a segmented multivariable Cox regression model. We also conducted subgroup analysis as well as analyzed the restricted cubic spline curves. Results After adjusting for all potential confounding factors, an increase of 1 mmol/L in lactate levels was found to be associated with an 17% rise in the 28-day hospital mortality risk among sepsis patients (HR: 1.17, 95% CI: 1.08-1.27, P = 0.0002). When considering lactate as a categorical variable, the mortality risk of patients with lactate levels ≥ 2.2 mmol/L was significantly increased (HR: 3.61, 95% CI: 1.24-10.54, P = 0.0189). The restricted cubic spline curve analysis revealed a nonlinear correlation between lactate and 28-day mortality, with an inflection point at 2.2 mmol/L. Similar findings were also observed in the assessment of secondary outcomes. Conclusions Our study demonstrates a non-linear correlation between lactate levels and 28-day mortality in pediatric sepsis, with a critical threshold of 2.2mmol/l for lactate levels in septic patients. Early assessment of lactate levels is recommended for children with sepsis to facilitate prompt intervention and mitigate the risk of fatality.